Una contribución al desarrollo de la educación rural - Aguilar Mora, Ma. Ester (2002)
This article presents the work carried out by the Division of Rural Education through the project Strengthening Rural Schools in Costa Rica and Central America. Information is provided to contextualize the project and its objectives are discussed. Mention is also made of some of its contributions to rural education.